(untitled) (Pesquisa Odontológica Brasileira, 2001)
This research was carried out in order to evaluate three radiographic methods - conventional periapical, digital periapical and panoramic - in the diagnosis of artificially produced periapical lesions. For this purpose, 5 mandibles, with lesions produced by means of spherical drills of different sizes, were used. The research was divided into five distinct phases, as follows: phase Z (initial) - characterized by the absence of lesion; phase R - lesion produced with a number 6 drill; phase J - lesion produced with a number 8 drill; phase D - lesion produced with a number 10 drill; and phase H - lesion reaching the vestibular cortex. The lesions were produced in quadrants. Radiographs were made after each phase and analyzed by 4 experts in radiology. For the digital system there was statistically significant difference in phase R (in the region of incisors) and in phase H (in the region of premolars). In the region of molars there was statistically significant difference in phase D for panoramic radiography. It must be pointed out that panoramic radiography produced the less effective results in phase H.